Arsenic detoxification potential of aox genes in arsenite-oxidizing bacteria isolated from natural and constructed wetlands in the Republic of Korea - Chang, Jin-Soo; Yoon, In-Ho; Lee, Ji-Hoon; Kim, Ki-Rak; An, Jeongyi; Kim, Kyoung-Woong (Environmental geochemistry and health, 2010)
Arsenic is subject to microbial interactions, which support a wide range of biogeochemical transformations of elements in natural environments such as wetlands. The arsenic detoxification potential of the bacterial strains was investigated with the arsenite oxidation gene, aox genotype, which were isolated from the natural and constructed wetlands. The isolates were able to grow in the presence of 10 mM of sodium arsenite (As(III) as NaAsO₂) and 1 mM of d+glucose. Phylogenetic analysis based on 16S rRNA gene sequencing indicated that these isolated strains resembled members of the genus that have arsenic-resistant systems (Acinetobacter sp., Aeromonas sp., Agrobacterium sp., Comamonas sp., Enterobacter sp., Pantoea sp., and Pseudomonas sp.) with sequence similarities of 81-98%. One bacterial isolate identified as Pseudomonas stutzeri strain GIST-BDan2 (EF429003) showed the activity of arsenite oxidation and existence of aoxB and aoxR gene, which could play an important role in arsenite oxidation to arsenate. This reaction may be considered as arsenic detoxification process. The results of a batch test showed that P. stutzeri GIST-BDan2 (EF429003) completely oxidized in 1 mM of As(III) to As(V) within 25-30 h. In this study, microbial activity was evaluated to provide a better understanding of arsenic biogeochemical cycle in both natural and constructed wetlands, where ecological niches for microorganisms could be different, with a specific focus on arsenic oxidation/reduction and detoxification.